2021
DOI: 10.1111/gcb.15883
|View full text |Cite
|
Sign up to set email alerts
|

Global gross nitrification rates are dominantly driven by soil carbon‐to‐nitrogen stoichiometry and total nitrogen

Abstract: Soil gross nitrification (GN) is a critical process in the global nitrogen (N) cycle that results in the formation of nitrate through microbial oxidation of ammonium or organic N, and can both increase N availability to plants and nitrous oxide emissions. Soil GN is thought to be mainly controlled by soil characteristics and the climate, but a comprehensive analysis taking into account the climate, soil characteristics, including microbial characteristics, and their interactions to better understand the direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
62
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(72 citation statements)
references
References 122 publications
(151 reference statements)
10
62
0
Order By: Relevance
“…Furthermore, higher soil DOC, SOC and TN concentrations stimulated by RSD which in turn also affected soil pH and bacterial abundance led to increased M and therefore higher NH 4 + production. This is in line with the general observation that a higher NH 4 + production via M is also enhancing O NH4 , explaining the close correlation between O NH4 and M (Elrys et al 2021b).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, higher soil DOC, SOC and TN concentrations stimulated by RSD which in turn also affected soil pH and bacterial abundance led to increased M and therefore higher NH 4 + production. This is in line with the general observation that a higher NH 4 + production via M is also enhancing O NH4 , explaining the close correlation between O NH4 and M (Elrys et al 2021b).…”
Section: Discussionsupporting
confidence: 91%
“…Generally, soil N mineralization dominates NH 4 + production and is a key factor affecting O NH4 (Elrys et al 2021b;Schimel and Bennett 2004). In this study, Soil gross N mineralization (M) was signi cantly higher in RSD compared to CK and affected by plants (Fig.…”
Section: Discussionmentioning
confidence: 55%
“…Therefore, it is reasonable to accept that GNM and GN rates are main stimulators of I NH4 and I NO3 (Booth et al, 2005; Wang et al, 2016). Previous studies also showed that MB, soil total N, and soil bulk density (BD) play a key role in controlling GNM and GN globally (Booth et al, 2005; Elrys, Ali, et al, 2021; Elrys, Wang, et al, 2021). Climatic factors and soil pH also play a role because they influence soil substrate (total C and N) availability and MB (Elrys, Wang, et al, 2021; Li et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, denitrification is a sequential reduction by which NO 3 – is reduced to N 2 O and/or dinitrogen gas (N 2 ) via NO 2 – and nitric oxide (NO), which are catalyzed by a series of enzymes that include copper-containing nitrite reductase and cytochrome cd1-containing nitrite reductase. In addition, studies have shown that nitrogen fertilization affects these processes by affecting the soil microbial characteristics ( Elrys et al, 2021 ). Meanwhile, some functional genes have been used as molecular markers to investigate the dynamics of microbial communities responsible for specific nitrogen transformation processes in various environments, including field soils ( Petersen et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%